Creating Community Connections and Partnerships for Transformative Social Change (LEARNing Landscapes, 2016)
In this article, I share my experiences connecting with community as a high school teacher, a community literacy developer, and a teacher educator. I describe three partnerships that created conditions for transformative change, challenging boundaries of traditional schooling by providing spaces for shared knowledge and meaning making. The experiences that undergird these partnerships present a counter story to de cit discourses and narratives of school failure. They highlight possibilities for investing in our collective future and demonstrate the capacity of individuals to build community and enact learning landscapes to bring about a more socially just world.
Keywords: community; literacy; transformative change; teacher education; social justice; narrative